Pemberdayaan Guru Sd untuk Merancang Projek Edukasi Lingkungan Berkelanjutan sebagai Langkah Nyata Menuju SDGs di Indragiri Hulu - Mahmud Alpusari; M. Nur Mustafa; Eva Astuti Mulyani; Guslinda Guslinda; Muhammad Fendrik; Mitha Dwi Anggriani (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2025)
This community service activity was carried out at Gugus 3 Public Elementary School, Pasir Penyu District, Indragiri Hulu Regency, with the aim of empowering elementary school teachers in designing sustainable environmental education projects based on local potential. Teachers in this area still face limitations in learning resources, understanding of environmental issues, and teaching media that are contextual to students' lives. This program is designed to increase teachers' capacity in developing and implementing environmental education pocketbooks as relevant thematic learning media and supporting the achievement of the Sustainable Development Goals (SDGs). The implementation of this community service activity is carried out through four main stages: planning, implementation, training, and evaluation. Each stage is interconnected and makes a significant contribution to program achievements. The training combines theory, discussion, and direct practice so that teachers are able to integrate environmental issues into learning. Evaluation results show that the program received a very positive response from participants with an average satisfaction score of 91.08%. Teachers reported an increase in understanding of sustainability principles, skills in designing teaching media, confidence in developing pocketbooks, and motivation to involve students in environmental projects. Although there are still challenges in the form of limited resources, this activity has proven effective in strengthening the role of teachers as agents of change in forming an environmentally aware generation and encouraging the realization of sustainable development in the region.